A207 RIPK2 AND AMPK AS EMERGING THERAPEUTIC TARGETS FOR INFLAMMATORY BOWEL DISEASE - Guo, Y (J Can Assoc Gastroenterol, 2020)
BACKGROUND: Persistent inflammation can trigger altered epigenetic, inflammation and bioenergetics states. Inflammatory bowel disease (IBD) is a heterogeneous disease with an abnormal inflammatory state and subsequent metabolic syndrome disorder. Current IBD therapeutics are directed to inhibit inflammatory pathways, such as inflammation of the epithelial cells in the colonic crypts. We hypothesize that in order to achieve mucosal healing and to keep patients in remission we must (i) inhibit inflammatory mediators and (ii) resolve secondary effects of inflammation such a reset of metabolic dysfunction. AIMS: The aims of this study are to explore correlations between inflammation/metabolic markers and the severity of the disease to uncover emerging new therapeutic players. METHODS: More than one hundred patients were recruited and underwent colonoscopy. In order to explore how biomarkers change with disease and time, all patients had IBD for more than 10 years or less than 5 years. Those diagnosed with cancer, celiac sprue, or diabetes were excluded. The activity of key metabolic markers (such as AMPK) was tracked using phospho-specific antibodies. Immunohistochemistry and immunoblotting were carried out, as described by Gordon et al., PLOSone 2013. All patients were consented under our IBD ethics protocol (Pro00001523 and Pro00077868). RESULTS: Using intestinal biopsies from non-IBD, UC and CD patients, we explored the expression/activation levels of markers of inflammation (such as obligate NOD2 kinase RIPK2) and metabolism (AMPK) in order to gain insight into correlations with clinical severity of the disease. We confirm that the loss in the activity of AMPK occurs with a gain of activity of RIPK2 that drives the inflammatory phenotype of the gut in patients with long-standing IBD (>10 years). (If inflammation is inhibited in a mouse model of IBD, metabolic reset occurs to regain AMPK and promote mucosal healing). However, RIPK2 remains elevated in patients that are currently on IBD therapeutics. CONCLUSIONS: Therapeutics inhibiting inflammation (RIPK2) and stimulating metabolic (AMPK) drivers of the disease may be a useful combination therapy to completely eliminate inflammation, reset abnormal metabolism and achieve full remission in IBD patients with longstanding disease. FUNDING AGENCIES: None